2008
DOI: 10.1038/sj.cgt.7701112
|View full text |Cite
|
Sign up to set email alerts
|

An improved human carboxylesterase for enzyme/prodrug therapy with CPT-11

Abstract: CPT-11 is a potent antitumor agent that is activated by carboxylesterases (CE) and intracellular expression of CEs that can activate the drug results in increased cytotoxicity to the drug. As activation of (1-piperidino)-1-piperidino]carbonyloxycamptothecin) by human CEs is relatively inefficient, we have developed enzyme/prodrug therapy approaches based on the CE/CPT-11 combination using a rabbit liver CE (rCE). However, the in vivo application of this technology may be hampered by the development of an immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 25 publications
(36 reference statements)
1
62
0
Order By: Relevance
“…If the immunogenic potential of the vector or the transgene prohibits clinical use, obvious alternative are to use 'empty vectors', to delete immunogenic sequences not required for protein function, or to 'humanize' immunogenic domains of non-human coding sequences, as has been reported for the rabbit CE that efficiently activates the prodrug irinotecan. 114 Until conditions are identified that permit unlimited expansion of clonal populations of autologous primary cells engineered to express a therapeutic of interest, wellcharacterized cell lines are most likely to have clinical utility.…”
Section: Immunogenicitymentioning
confidence: 99%
“…If the immunogenic potential of the vector or the transgene prohibits clinical use, obvious alternative are to use 'empty vectors', to delete immunogenic sequences not required for protein function, or to 'humanize' immunogenic domains of non-human coding sequences, as has been reported for the rabbit CE that efficiently activates the prodrug irinotecan. 114 Until conditions are identified that permit unlimited expansion of clonal populations of autologous primary cells engineered to express a therapeutic of interest, wellcharacterized cell lines are most likely to have clinical utility.…”
Section: Immunogenicitymentioning
confidence: 99%
“…Control nontransduced HB1.F3.CD cells were cultured under identical conditions. Adenoviral stock for each virus type, AdrCE [20] or AdhCE1m6 [24], was diluted in media and added to cells to give a final multiplicity of infection (MOI) of 20. NSCs were incubated for 18 -24 hours, washed with phosphate-buffered saline (PBS), trypsinized, and resuspended in fresh culture medium.…”
Section: Neural Stem Cell Culturementioning
confidence: 99%
“…Finally, tumorlocated expression of carboxylesterase, responsible for the catalytic hydrolysis of CPT-11 to SN-38, can sensitize tumor cells to CPT-11 in vitro and in vivo. 49,50 As carboxyesterases act on CPT-11 whereas bG acts on SN-38G, combined treatment with Ad.bG and Ad.carboxyesterase vectors may offer a rationale method to further enhance the antitumor efficacy of CPT-11.…”
mentioning
confidence: 99%